Design for human safety in manufacturing systems: applications of design theories, methodologies, tools and techniques. Issue 12 (1st December 2016) - Sadeghi, Leyla; Dantan, Jean-Yves; Siadat, Ali; Marsot, Jacques
ABSTRACT: During recent decades, there has been growing awareness of human safety in the design process. The purpose of this paper is to review the literature on design for human safety (DfHS) in manufacturing systems. To this end, a process for systematically reviewing DfHS studies was used. The authors focused in particular on the applications of design theories and methodologies (DTM) and design tools and techniques (DTT) to analyse and identify work situations in order to improve human safety in manufacturing system design. The authors also tried to identify the design phases in which these DTM and DTT could be applied. This research review covered papers published between 1980 and 2015, and combined seven groups of terms: DfHS, design, safety, DTM, DTT, risk and working situation. A critical analysis was also performed in view to defining a research agenda and the most prominent key actions capable of pointing out paths for future research.